Investigation of „childish" thinking in adults - Navickas, V. (Psichologija, 1991)
This article deals with the causes of the manifestation of the analogues of „Piaget phenomena" in adults’ thinking. It states that the investigation of this problem requires a thorough choice of tasks, the need of paying attention to the subjective degree of their difficulty. Results of the investigation, carried out by using the modified variants of N. A. Podgoretskaya’s methods, show that the existence of manifestations of „childish" thinking in adults does not allow, however, conclusions to be made that the intellect of adults has not reached the level of formal operations yet. Thus, the main conclusions of N. A. Podgoretskaya’s works are to be challenged.